Sociolinguistics and corpus linguistics - Baker, Paul, 1972- (Edinburgh sociolinguistics., 2010)
This textbook introduces students to the ways in which techniques from corpus linguistics can be used to aid sociolinguistic research. Corpus linguistics shares with variationist sociolinguistics a quantitative approach to the study of variation or differences between populations. It may also complement qualitative traditions of enquiry such as interactional sociolinguistics. This text covers a range of different topics within sociolinguistics:*Analysing demographic variation*Comparing language use across different cultures*Examining language change over time*Studying transcripts of spoken inte.